ANALISA KAPASITAS APRON PADA JAM SIBUK DI BANDAR UDARA YOGYAKARTA INTERNASIONAL KULON PROGO - Devi Nurfiani; Ahmad Musadek; Bambang Wasito (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The high interest in tourist visits and economic development in the Special Region of Yogyakarta, led to an increasing surge in passengers resulting in an increase in scheduled commercial flights. So that flight activity, especially in the apron is increasing during peak hours. It can certainly cause a meaningful impact, which can cause flight delays, queues to land or take off that can cause losses for the airline and the airport. The method in this study used quantitative research method and JICA/Japan International Corporation Agency (1991) to calculate apron capacity and aircraft movement during peak hours. The movement of aircraft during peak hours occurs in March 2021 as many as 3 aircraft per hour, while the aircraft movement capacity that can be accommodated apron is 4 aircraft per hour. The average percentage of aircraft movement during the period of a year is 2.03% from April 2020 to March 2021.